Pengaruh Kualitas Pelayanan Dan Strategi Promosi Terhadap Kepuasan Nasabah BCA - Deborah Ananda Gosal (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Bank Central Asia Tbk is one of the leading private banks in Indonesia that has been recognized by the wider community among the many banks in Surabaya City, a very professional management team and an extensive network. Bank BCA as a transactional bank that offers a range of banking services that have Cash and Non-Cash ATMs provided in various strategic locations throughout Indonesia to meet the diverse needs of customers. This study aims to determine the effect of service quality on customer satisfaction and promotional strategies on customer satisfaction. The type of research used is quantitative research and the sampling technique is purposive sampling technique with the number of samples obtained based on criteria and data analysis techniques using SEM Amos. This research was conducted by distributing questionnaires through 100 respondents. The results showed that service quality has a significant positive effect on customer satisfaction for BCA Veteran Surabaya Bank customers and promotional strategies have a significant positive effect on customer satisfaction for BCA Veteran Surabaya Bank customers.